Assessment of content and chemical forms of arsenic, copper, lead, and chromium in sewage sludge compost as affected by various bulking agents - Saffari Mahboub (Main Group Metal Chemistry, 2020)
In current study, the effect of various organic substances as bulking agents (BAs) including wheat straw, pistachio hull wastes, and tree leaves at different levels (10, 25, 45% v/v) were investigated on total concentration and chemical forms of Cu, Pb, Cr, and As in sewage sludge (SS) compost prepared by windrow method. According to the results, the composting process (with/without BAs), due to losses of SS mass and volume, increased the total concentration of heavy metals (HMs) compared to the un-composted SS sample (RSS). Evaluation of HMs chemical forms in prepared compost sample without BAs application (CSS) showed that the composting process reduced the mobility factor of As (from 28% to 20%), Pb (from 11.6% to 9.3%), and Cr (from 14.5% to 9.2%) compared to the RSS. Application of three BAs considerably decreased the mobility factor of As (17.5-18.8%), Pb (4.8-7.9%), and Cr (1.4-6.8%) compared to CSS and RSS. Changes of Cu mobility in prepared compost samples showed an unclear trend, however in some treatments, due to transferred organic fraction into exchangeable and carbonate fractions, increasing of this factor was obvious. Generally, the composting appeared to reduce As, Pb, and Cr availability by stabilizing the three metals and making them more stable and less mobile. In addition, the BAs application effect on HMs behavior of SS compost samples were so different and no specific kind of BAs can be recommended as a superior BAs in SS composting process.